High cathelicidin levels are associated with Hashimoto's thyroiditis (Annals of Medical Research, 2023)
Aim: Hashimoto's thyroiditis (HT) is a common chronic autoimmune thyroid disease. Many studies on autoimmune diseases have investigated human cathelicidin from the anti-microbial peptide family. This article aims to determine the level of cathelicidin in Hashimoto's thyroiditis and evaluate its relationship with thyroid functions.Materials and Methods: Eighty-eight subjects were included in the study. Gender, age, and BMI were similar between 48 HT patients and 40 healthy controls. Cathelicidin levels were studied in serum samples with an ELISA kit.Results: There were euthyroid and subclinical hypothyroid HTs in the study. There was a significant difference between the controls and patients in terms of TSH (p